Long-Term Outcomes and Factors Associated with Mortality in Patients with Moderate to Severe Pulmonary Hypertension in Kenya - Mzee Ngunga; Abdulaziz Mansur Abeid; Jeilan Mohamed; Anders Barasa (Ubiquity Press, 2020)
Background: Pulmonary hypertension is poorly studied in Africa. The long-term survival rates and prognostic factors associated with mortality in patients with moderate to severe pulmonary hypertension (PH) in Africa are not well described. Objectives: To determine the causes of moderate to severe PH in patients seen in contemporary hospital settings, determine the patients' one-year survival and the factors associated with mortality following standard care. Methods: A retrospective review of patients diagnosed with moderate to severe PH at Aga Khan University Hospital (AKUHN) from August 2014 to July 2017 was carried out. Clinical and outcome data were collected from medical records and the hospital mortality database. Telephone interviews were conducted for patients who died outside the hospital. Survival analysis was done using Kaplan-Meier, and log-rank tests were used to assess differences between subgroups. Cox regression modelling with multivariable adjustment was used to identify factors associated with all-cause mortality. Results: A total of 659 patients with moderate to severe PH were enrolled. Median follow-up time was 626 days. The survival rates of the patients at 1 and 2 years were 73.8% and 65.9%, respectively. The following variables were significantly associated with mortality: diabetes mellitus [adjusted HR 1.52, 95% CI (1.14-2.01)], WHO functional class III/IV [adjusted HR 3.49, 95% CI (2.46-4.95)], atrial fibrillation [adjusted HR 1.53, 95% CI (1.08-2.17)], severe PH [adjusted HR 1.72, 95% CI (1.30-2.27)], right ventricular dysfunction [adjusted HR 2.42, 95% CI (1.76-3.32)] and left ventricular dysfunction [adjusted HR 1.91, 95% CI (1.36-2.69)]. Obesity [adjusted HR 0.68, 95% CI (0.50-0.93)] was associated with improved survival. Conclusion: Pulmonary hypertension is associated with poor long-term outcomes in African patients. Identification of prognostic factors associated with high-risk patients will assist in patient management and potentially improved outcomes.